A network perspective on assessing system architectures: Robustness to cascading failure. Issue 5 (22nd July 2020) - Potts, Matthew W.; Sartor, Pia A.; Johnson, Angus; Bullock, Seth
Abstract: Despite a wealth of system architecture frameworks and methodologies available, approaches to evaluate the robustness and resiliency of architectures for complex systems or systems of systems are few in number. As a result, system architects may turn to graph‐theoretic methods to assess architecture robustness and vulnerability to cascading failure. Here, we explore the application of such methods to the analysis of two real‐world system architectures (a military communications system and a search and rescue system). Both architectures are found to be relatively robust to random vertex removal but more vulnerable to targeted vertex removal. Hardening strategies for limiting the extent of cascading failure are demonstrated to have varying degrees of effectiveness. However, in taking a network perspective on architecture robustness and susceptibility to cascade failure, we find several significant challenges that impede the straightforward use of graph‐theoretic methods. Most fundamentally, the conceptualization of failure dynamics across heterogeneous architectural entities requires considerable further investigation.